ANALISIS STRUKTUR JARINGAN KOMUNIKASI DALAM ADAPTASI EKONOMI, SOSIAL DAN BUDAYA PADA PAGUYUBAN BABUL AKHIRAT DI KOTA BATAM - Ageng Rara Cindoswari (Jurnal Komunikasi, 2016)
ABSTRACTThe purposes of this study include : (1) To know the communication network on the Babul Akhirat community in the economic, social, and cultural adaptation; (2) To identify individual roles in thecommunication network of the Babul Akhirat community in the economic, social, and culturaladaptation; and (3) To describe the communication network centrality of the Babul Akhirat community in the economic, social, and cultural adaptation. This study constitutes a descriptive research with the quantitative approach. The study design of communication network is a complete network andthe focus of this study was at the system level. In this study, the researcher referred to the nominalistapproach by viewing the study population. The actor determination in this study was based on thepositional strategy, namely the Babul Akhirat Community in Batam City where the actors becomingsamples of the population were members of the Babul Akhirat community. Sampling used in this studywas the samples of small groups, that were all members of the Babul Akhirat community, amounted to82 members. This study used the analysis technique of sociometric data and the communication networkstructures by using by using UCINET VI. The results of this study showed: (1) The social and economiccommunication network took possession of the interlocking network structure; (2) The individual rolesin the communication network of the Babul Akhirat community in the economic, social, and culturaladaptation encompassed opinion leader, cosmopolite, and bridge; and (3) The actors representing thehighest local centrality value for the communication network of economic adaptation were node 15, 22,30, and 59, while values of the communication network for the social adaptation were node 22 and 31,and values of the network communication for the cultural adaptation were node 30, 47, and 45. On theother result, actors representing the lowest global centrality value for each communication network ofeconomic adaptation, social adaptation, and cultural adaptation were node 23, node 5, and node 13. Keywords: Communication Network Structure, Actor, Babul Akhirat Community